Konsep Parenting Dalam Sholat - Fatma Sari (IAIN Sorong, 2019)
Parenting is a process of educating a person on an ongoing basis so that someone is able to know himself, develop his potential and be responsible for himself. Educating is a very important thing to be trained and displayed by educators and parents because this will have a good impact on students and our children. Besides being important, children and students are responsibilities that must be accounted for before God Almighty. in the hereafter. Therefore, it has become our need to pay off those responsibilities by educating our children and students well and by paying attention to the principles of parenting. Prayer is the process of upbringing/parenting that Allah SWT. A gift to save people, a complex process so that humans can improve their quality. In prayer there are preventive, curative, and constructive functions, which are carried out repeatedly throughout human life, to train ourselves and our souls to be better in terms of quantity and quality.